Zebularine enhances apoptosis of human osteosarcoma cells by suppressing methylation of ARHI. Issue 12 (19th December 2016) - Ye, Kaishan; Wang, Shuanke; Wang, Jing; Han, Hua; Ma, Bing; Yang, Yong
Abstract : ARHI is an imprinted tumor suppressor gene and its methylation suppresses ARHI transcription levels to cause the development and progression of malignant tumors. Zebularine exerts a demethylation function for tumor suppressor genes. Our study aims to investigate the effect and mechanism of action of zebularine on the epigenetic modification of the ARHI gene, and whether this effect may modulate the viability and apoptosis of human osteosarcoma cells. We found that zebularine inhibited the viability and promoted apoptosis in osteosarcoma cells. Zebularine potentiated the expression of ARHI at both the protein and mRNA level. This was related to the downregulation of methylation of ARHI caused by zebularine. Zebularine suppressed the interaction of DNA methyltransferase 1 (DNMT1) with histone methyltransferase G9a, but had no effect on G9a alone. Knockdown of DNMT1 or G9a can induce a reduction of ARHI methylation. Therefore, we inferred that zebularine was likely to directly repress DNMT1 alone, but G9a was necessary to regulate the function of DNMT1 on ARHI methylation. Moreover, knockdown of ARHI rescued cell viability and apoptosis under the zebularine‐treated condition. We showed that zebularine inhibited viability and promoted apoptosis by disturbing the interaction between DNMT1 and G9a, thereby resulting in lower ARHI methylation and elevated ARHI expression in osteosarcoma cells. Abstract : ARHI is an imprinted tumor suppressor gene and its methylation suppresses ARHI transcription levels to cause the development and progression of malignant tumors. Zebularine exerts demethylation function for tumor suppressor genes. Our study aims to investigate the effect and mechanism of action of zebularine on the epigenetic modification of the ARHI gene, and whether this effect may modulate the viability and apoptosis of human osteosarcoma cells.